2021
DOI: 10.1186/s12937-021-00717-1
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in relation to the risk of hypertension among Iranian adults: cross-sectional analysis of Fasa PERSIAN cohort study

Abstract: Background Hypertension is a common chronic disease with various complications and is a main contributing factor to cardiovascular disease (CVD). This study aimed to assess the association of diet quality, assessed by dietary diversity score (DDS), Mediterranean dietary score (MDS), diet quality index-international (DQI-I), and healthy eating index-2015 (HEI-2015) with the risk of hypertension. Methods This study recruited a total of 10,111 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…For instance, a study by Motamedi et al on the Fasa cohort data showed that the Mediterranean dietary score and a healthy eating index-2015 was associated with a lower risk of having hypertension. They also indicated that higher adherence to the Mediterranean dietary score and healthy eating index-2015 was associated with a decrease in the obesity-related parameters, including weight, Waist circumference, BMI, and hip circumference [ 52 ]. Furthermore, isoflavones in plant-based diets, which regulate the expression of sterol regulatory element-binding protein (SREBP)-2, improve cholesterol clearance from serum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study by Motamedi et al on the Fasa cohort data showed that the Mediterranean dietary score and a healthy eating index-2015 was associated with a lower risk of having hypertension. They also indicated that higher adherence to the Mediterranean dietary score and healthy eating index-2015 was associated with a decrease in the obesity-related parameters, including weight, Waist circumference, BMI, and hip circumference [ 52 ]. Furthermore, isoflavones in plant-based diets, which regulate the expression of sterol regulatory element-binding protein (SREBP)-2, improve cholesterol clearance from serum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension (HTN) is a global health problem, the principal cause of cardiovascular diseases (CVDs) and premature death, affecting roughly one billion adults worldwide [ 1 , 2 ]. By 2030, it is estimated that 41% of American adults will have been diagnosed with HTN [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…By 2030, it is estimated that 41% of American adults will have been diagnosed with HTN [ 3 ]. In contrast to the trends reported in the USA and northern Europe, evidence indicates that CVDs mortality is rising in Iran, and 24% of females and 22% of males suffer from HTN [ 4 , 2 ]. HTN is a multifactorial disease caused by a complex combination of dietary, lifestyle, and genetic risk factors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations